Effect of short-term mindfulness-based stress reduction on sleep quality in male patients with alcohol use disorder - Wang, Yongmei; Chen, Cuiping; Gu, Lina; Zhai, Yi; Sun, Yanhong; Gao, Guoqing; Xu, Yayun; Pang, Liangjun; Xu, Lianyin (Frontiers in Psychiatry, 2023)
Sleep disturbance is one of the most prominent complaints of patients with alcohol use disorder (AUD), with more than 70% of patients with AUD reporting inability to resolve sleep problems during abstinence. Mindfulness-based stress reduction (MBSR) has been shown to improve sleep quality and as an alternative therapy to hypnotics for sleep disorders. The aim of the present study was to evaluate the effect of short-term MBSR on sleep quality in male patients with AUD after withdrawal. A total of 91 male patients with AUD after 2 weeks of routine withdrawal therapy were randomly divided into two groups using a coin toss: the treatment group (n = 50) and control group (n = 41). The control group was received supportive therapy and the intervention group added with MBSR for 2 weeks on the basis of supportive therapy. Objective sleep quality was measured at baseline and 2 weeks after treatment using the cardiopulmonary coupling (CPC). Indicators related to sleep quality include total sleep time, stable sleep time, unstable sleep time, rapid eye movement (REM) sleep time, wake-up time, stable sleep latency, sleep efficiency, and apnea index. These indicators were compared by an analysis of covariance (ANCOVA) between the two groups, controlling for individual differences on the respective measures at baseline. The results showed that there were no significant differences in the age, BMI, educational status, years of drinking, daily intake, types of alcohol , scores of CIWA-AR, scores of SDS, or scores of SAS between the two groups. Moreover, compared with the control group, the total sleep time (F (1,88) = 4.788, P = 0.031) and stable sleep time (F (1,88) = 6.975, P = 0.010) were significantly increased in the treatment group. Furthermore, the average apnea index in the patients received MBSR was significantly decreased than in the control group (F (1,88) = 5.284, P = 0.024). These results suggest that short-term MBSR could improve the sleep quality and may serve as an alternative treatment to hypnotics for sleep disturbance in patients with AUD after withdrawal.